Synthesis of Vanadium Pentoxide using Hydrothermal Autoclave Approach - Amal Abbood; Ibraheem Ibraheem (مجلة جامعة الانبار للعلوم الصرفة, 2023)
The transition metal vanadium can easily move between the oxidation states +V, +IV, and +III and expand its sphere beyond tetrahedral coordination. It oxidizes into a brownish black trioxide, a blue-black tetroxide, or a reddish orange pentoxide when heated in air at various temperatures. The simple hydrothermal autoclave approach was used to synthesize vanadium pentoxide V2O5 nanoparticles from ammonium metavanadate NH4VO3. The synthesized sample was identification using X-Ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM) and atomic force microscopy (AFM). The result confirms forming of V2O5 nanoparticles and the diameter was around 61- 167 nm. The transition metal vanadium can easily move between the oxidation states +V, +IV, and +III and expand its sphere beyond tetrahedral coordination. It oxidizes into a brownish black trioxide, a blue-black tetroxide, or a reddish orange pentoxide when heated in air at various temperatures. The simple hydrothermal autoclave approach was used to synthesize vanadium pentoxide V2O5 nanoparticles from ammonium metavanadate NH4VO3. The synthesized sample was identification using X-Ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM) and atomic force microscopy (AFM). The result confirms forming of V2O5 nanoparticles and the diameter was around 61- 167 nm.